Intraperitoneal fipronil effects on liver histopathological, biochemistry and morphology in Caspian kutum, Rutilus frisii kutum (Kamenskii, 1901) - R. Alijani Ardeshir; H. Zolgharnein; A.A. Movahedinia; N. Salamat; E. Zabihi; J. Regenstein (Global Journal of Environmental Science and Management)
Fipronil is a relatively new insecticide in agriculture with health and environmental effects. This is the first report studying effect of fipronil on fish administered via intraperitoneal route. Intraperitoneal LD50  of fipronil in 16.3 g Caspian kutum, Rutilus frisii kutum, fingerlings was determined using a total of 133 fish in 19 tanks (7 fish/tank) including one control and 6 treatment groups (300, 450, 550, 650, 750, 850 mg/kg). Fish were injected intraperitoneally and monitored at 96 h. The LD50 of fipronil was 632 mg/kg in Caspian kutum. Sub-lethal test doses of 10, 20, and 30% of the LD50 at 96 h were used to assess the effect of fipronil on the fish’s liver.  The blood plasma of 90 fish were used (18 at each test dose and in controls) on days 7 and 14 for biochemistry. The hepatosomatic index (HSI) of the livers were obtained and histopathology done on the same days. Pyknosis, sinusoid dilation and vacuolization were common histological changes, and these changes became more severe in a time and dose dependent manner. This dependence was also observed for HSI and the liver biochemical test (alanine and aspartate transaminase). Liver histological alterations showed that fipronil can be a potential factor in liver carcinoma.